Decoupling Jihad from Boko-Haram Insurgency: A Critical Analysis of Misconceptions and Realities in Nigeria - Yusuph, Ismael Funsho; Abdulraheem, Taofeeq Abolaji; Abdulazeez, Abdurrozaq Opeyemi (Mazahibuna: Jurnal Perbandingan Mazhab, 2025)
The concept of Jihad is an essential Islamic doctrine often misrepresented and misunderstood, particularly in contemporary discourse. Jihad has a well-defined framework in Islamic law but insurgent groups such as Jama’atu Ahlis Sunnah Lida’awati wal Jihad in Nigeria, popularly known as Boko-Haram, claim to act under its banner. The situation raises concerns about the distortion of Jihad and subsequent conflation with insurgency. Therefore, this study aimed to critically examine the principles of Jihad under Islamic law and determine the possible connection to the activities of Boko-Haram. The analysis of misconceptions surrounding Jihad was to clarify its distinction from insurgency. This was achieved through the adoption of a qualitative method to analyze the classical and contemporary Islamic legal texts in order to establish the parameters of Jihad. Moreover, the principles were compared with the actions of Boko-Haram to determine whether their claims could be substantiated in Islamic jurisprudence. The results showed that the activities of Boko-Haram were not in line with the principles of Jihad as prescribed in Islamic law. However, their actions reflected the characteristics of insurgency which negated the ethical and legal framework of Jihad rooted in justice, equity, and moral conduct. This study contributed to the discourse on Jihad by systematically distinguishing the concept from insurgency through Islamic legal principles, offering a scholarly response to contemporary misinterpretations. The analysis further served as a foundation for future studies on religious misinterpretations in justifying violence and could also inform policy formulation, counter-radicalization tactics, and public awareness initiatives.